High activation levels maintained in receptor‐binding domain–specific memory B cells in people with severe coronavirus disease 2019. Issue 2 (1st December 2022) - Gupta, Money; Balachandran, Harikrishnan; Louie, Raymond H Y; Li, Hui; Agapiou, David; Keoshkerian, Elizabeth; Christ, Daniel; Rawlinson, William; Mina, Michael M; Post, Jeffrey J; Hudson, Bernard; Gilroy, Nicky; et al.
Abstract: The long‐term health consequences of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection are still being understood. The molecular and phenotypic properties of SARS‐CoV‐2 antigen–specific T cells suggest a dysfunctional profile that persists in convalescence in those who were severely ill. By contrast, the antigen‐specific memory B‐cell (MBC) population has not yet been analyzed to the same degree, but phenotypic analysis suggests differences following recovery from mild or severe coronavirus disease 2019 (COVID‐19). Here, we performed single‐cell molecular analysis of the SARS‐CoV‐2 receptor‐binding domain (RBD)–specific MBC population in three patients after severe COVID‐19 and four patients after mild/moderate COVID‐19. We analyzed the transcriptomic and B‐cell receptor repertoire profiles at ~2 months and ~4 months after symptom onset. Transcriptomic analysis revealed a higher level of tumor necrosis factor‐alpha (TNF‐α) signaling via nuclear factor‐kappa B in the severe group, involving CD80, FOS, CD83 and TNFAIP3 genes that was maintained over time. We demonstrated the presence of two distinct activated MBCs subsets based on expression of CD80 hi TNFAIP3 hi and CD11c hi CD95 hi at the transcriptome level. Both groups revealed an increase in somatic hypermutation over time, indicating progressive evolution of humoral memory. This study revealed distinct molecular signatures of long‐term RBD‐specific MBCs in convalescence, indicating that the longevity of these cells may differ depending on acute COVID‐19 severity. Abstract : We performed an in‐depth single‐cell gene expression analysis of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) receptor‐binding domain–specific memory B cells in three patients after severe coronavirus disease 2019 (COVID‐19) and four patients after mild/moderate COVID‐19. We analyzed the transcriptome and B‐cell repertoire at ~2 months and ~4 months after symptom onset. The transcriptomic analysis revealed that in the severe group, genes associated with activation, in particular, those associated with tumor necrosis factor‐alpha signaling via nuclear factor‐kappa B were maintained, whereas in the mild/moderate group these declined over time.